2017
DOI: 10.1016/j.rvsc.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic typing of bovine viral diarrhoea virus in cattle on Irish farms

Abstract: The genotype and subgenotype was established for 325 field viruses and one commercial vaccine viral strain based on the analysis of at least one genomic region. BVDV-1a was the prominent subgenotype (n=317) with BVDV-1b (n=6), BVDV-1d (n=1) and BVDV-1e (n=1) also observed. A number of nucleotide sequence alignments and phylogenetic trees were constructed to represent the relationship between Irish field viruses and reference strains representative of all known BVDV genotypes and subgenotypes. Evidence of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 132 publications
(255 reference statements)
0
7
0
Order By: Relevance
“…▲ : Isolates from different clusters, but given the same name. References (I): [21,49,114,115,116]; (II): [41,49]; (III): [117]; (IV): [118]; (V): [119,120]; (VI): [52]; (VII): [21,49,121]; (VIII): [122,123,124,125,126]; (IX): [21]; (X): [127,128,129]; (XI): [21,49,130,131,132,133,134,135,136,137,138,139,140]; (XII): [141]; (XIII): [142,143]; (XIV): [144]; (XV): [21,49,52]; (XVI): [145,146]; (XVII): [21,40,147,148,149,150,151,152]; (XVIII): [153]; (XIX): [9,154,155,156]; (XX): [157,158,159,160,161,162]; (XXI): […”
Section: Figurementioning
confidence: 99%
“…▲ : Isolates from different clusters, but given the same name. References (I): [21,49,114,115,116]; (II): [41,49]; (III): [117]; (IV): [118]; (V): [119,120]; (VI): [52]; (VII): [21,49,121]; (VIII): [122,123,124,125,126]; (IX): [21]; (X): [127,128,129]; (XI): [21,49,130,131,132,133,134,135,136,137,138,139,140]; (XII): [141]; (XIII): [142,143]; (XIV): [144]; (XV): [21,49,52]; (XVI): [145,146]; (XVII): [21,40,147,148,149,150,151,152]; (XVIII): [153]; (XIX): [9,154,155,156]; (XX): [157,158,159,160,161,162]; (XXI): […”
Section: Figurementioning
confidence: 99%
“…Genetic diversity of strains in Ireland is limited, with the majority being BVDV-1a (>95% in three studies) followed by BVDV-1b, with single isolates assigned to BVDV-1d and BVDV-1e. There are no reports of BVDV-2 (41)(42)(43). Given that the inactivated vaccines predominantly used in the programme both contain BVDV-1a strains, antigenic divergence between field and vaccine strains should therefore not be an issue.…”
Section: Calf Prevalencementioning
confidence: 99%
“…This finding contrasts with Guelbenzu‐Gonzalo et al., 10 who found that BVDV‐1a predominated throughout NI. Interestingly, O'Brien et al 9 . found BVDV‐1e to be circulating throughout the Republic of Ireland, with which Enniskillen shares a border.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Clinical signs of acute infection include fever, diarrhoea and reproductive issues. 8,9 Fetuses infected in utero between 30 and 125 days of gestation may be born persistently infected (PI) and, since they shed large quantities of the virus throughout their lives, constitute a significant threat to other animals and disease control. 8 Guelbenzu-Gonzalo et al 10 conducted a genotypic survey of BVDV in cattle in Northern Ireland (NI) from 1999 to 2011, which showed that the genotype BVDV-1a predominated and detected the presence of genotype BVDV-1b for the first time.…”
Section: Introductionmentioning
confidence: 99%